ANALISIS STATUS HUKUM ISTRI DAN ANAK SETELAH PENOLAKAN ISBAT CERAI: STUDI KASUS PENGADILAN AGAMA KUNINGAN NO. 1461/PDT.G/2022/PA.KNG - Hidayat, Yayat; Rumaisah, Rima (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2024)
The matter of isbat divorce or better known as isbat marriage cumulation divorce lawsuit whose application was not accepted, is a very important issue to be discussed. Because in Islamic law marriage registration is not a condition for the validity of the marriage, whereas in positive law it is included in the conditions for the validity of the marriage. Failure to accept the divorce law will have an impact on the status of the wife, especially the children resulting from the marriage. The bad consequence of not accepting the divorce law is that both the wife and children will find it difficult to obtain the rights they should receive, such as maintenance rights, hadhanah rights and other rights. The aim of this research is to find out the judge's considerations in the case of the application for a divorce order not being accepted in the ruling of the Kuningan Religious Court No.1461/Pdt.G/2022/PA.Kng. Then analyze how the status of the wife and children as a result of the divorce application being rejected is reviewed according to Islamic law and positive law. This research uses qualitative methods and the type of research used by the author is a combined type of research, because the author combines library data with field data. The data collection technique carried out by the author uses documentation data collection techniques. The data analysis technique used by the author is descriptive analysis technique. The results of this research include: first, the judge's considerations in case number 1461/Pdt.G/2022/PA.Kng were not accepted, based on the judge's considerations in general, Law No. 5 of 2009, article 9 of Law No. 1 of 1974, Article 42 KHI, and Law No. 3 of 2006 which was strengthened by the failure to register the marriage of the defendant and plaintiff at the KUA. Second, based on a review of the positive law that applies in Indonesia, namely article 9 of Law No. 1 of 1989, article 9 of Law No. 1 of 1974, Article 2 paragraph 1 of the Marriage Law, the status of women who marry in an unregistered marriage is not considered a legal wife, nor are children who born from this marriage has the status of an illegitimate child as well. Third, based on a review of Islamic law, in cases where the marriage isbat is not granted, it does not affect the validity of the marriage that has been carried out, and the divorce process by means of khuluk or contested divorce can still be pursued and has sharia legal consequences related to it. Divorce creates a new status, for the wife changes to a woman who is no longer married or a widow, while the status of the child remains a legitimate child, because he was born from a valid marriage according to Islamic law.